Experimental Evolution and Economics. (19th November 2015) - Burnham, Terence C.; Dunlap, Aimee; Stephens, David W.
This is a theory paper that advocates experimental evolution as a novel approach to study economic preferences. Economics could benefit because preferences are exogenous, axiomatic, and contentious. Experimental evolution allows the empirical study of preferences by placing organisms in designed environments and studying their genotype and phenotype over multiple generations. We describe a number of empirical studies on different aspects of preferences. We argue that experimental evolution has the potential to improve economics.